Depth profiling analysis of HfON on SiON ultrathin films by parallel angle resolved x‐ray photoelectron spectroscopy and medium energy ion scattering. (22nd January 2016) - Fauquier, Laurent; Pelissier, Bernard; Jalabert, Denis; Pierre, François; Doloy, Delphine; Beitia, Carlos; Baron, Thierry
Abstract : The high‐k metal gate (HKMG) film stacks introduced because 32 nm node of complementary metal oxide semiconductor (CMOS) is one major case where composition determination is mandatory. In this work, two high‐resolution chemical depth profiling characterization techniques, the parallel angle‐resolved X‐ray photoelectron spectroscopy (pARXPS) and the medium energy ion scattering (MEIS), are used to determine with accuracy the composition of HfON/SiON (high‐k/interfacial layer) stack from the 14 nm node technology. The pARXPS measurements reveal that the nitrogen distribution presents a gradient toward the Si substrate, and the MEIS results show that there is no interfacial HfSiON layer between the HfON and the SiON layers. Moreover, these two techniques show that the HfON layer is sub‐stoichiometric. The combination of the information obtained from both pARXPS and MEIS was actually found very valuable to determine undoubtedly the chemical profile. Copyright © 2016 John Wiley & Sons, Ltd.